Comparing Upper Airway Stimulation to Transoral Robotic Base of Tongue Resection for Treatment of Obstructive Sleep Apnea. (12th September 2018) - Huntley, Colin; Topf, Michael C.; Christopher, Vanessa; Doghramji, Karl; Curry, Joseph; Boon, Maurits
Abstract : Objectives: Transoral robotic surgery (TORS) and upper airway stimulation (UAS) are modalities for treating tongue base obstruction contributing to obstructive sleep apnea (OSA). We aim to compare patients with OSA undergoing TORS to those undergoing UAS. Methods: We retrospectively reviewed patients treated with TORS and UAS using the senior authors' surgical database. We evaluated demographic, preoperative polysomnography (PSG), postoperative PSG, complication, hospital length of stay, and hospital readmission data to compare the two cohorts. Results: Seventy‐six patients underwent UAS. This included 50 men and 26 women. The mean age and body mass index were 61.92 and 29.38. The mean pre‐ versus postoperative apnea hypopnea index (AHI) and O2 nadir were 36.64 versus 7.20 and 80.27% versus 88.77%, respectfully. The rate of surgical success and postoperative AHI less than 15 and 5 were 86.84%, 89.47%, and 59.21. All patients underwent ambulatory surgery, and no one was readmitted. Twenty‐four patients underwent TORS. This included 20 men and four women with a mean age and body mass index BMI of 46.42 and 29.63. The mean pre‐ versus postoperative AHI and O2 nadir were 35.70 versus 20.05 and 80.50% versus 84.10%, respectfully. The rate of surgical success and postoperative AHI less than 15 and 5 were 54.17%, 50.00%, and 20.83%. The mean length of stay was 1.33 days, and four patients were readmitted. We found significant differences in age, postoperative AHI and O2 nadir, surgical success and postoperative AHI less than 15 and 5, length of stay, and rate of readmission. Conclusions: UAS is successful in treating OSA showing improved outcomes, length of stay, and readmission compared to TORS. Level of Evidence: 3 Laryngoscope, 129:1010–1013, 2019